Bayesian joint modeling of bivariate longitudinal and competing risks data: An application to study patient‐ventilator asynchronies in critical care patients. Issue 6 (11th August 2017) - Rué, Montserrat; Andrinopoulou, Eleni‐Rosalina; Alvares, Danilo; Armero, Carmen; Forte, Anabel; Blanch, Lluis
Abstract: Mechanical ventilation is a common procedure of life support in intensive care. Patient‐ventilator asynchronies (PVAs) occur when the timing of the ventilator cycle is not simultaneous with the timing of the patient respiratory cycle. The association between severity markers and the events death or alive discharge has been acknowledged before, however, little is known about the addition of PVAs data to the analyses. We used an index of asynchronies (AI) to measure PVAs and the SOFA (sequential organ failure assessment) score to assess overall severity. To investigate the added value of including the AI, we propose a Bayesian joint model of bivariate longitudinal and competing risks data. The longitudinal process includes a mixed effects model for the SOFA score and a mixed effects beta regression model for the AI. The survival process is defined in terms of a cause‐specific hazards model for the competing risks death or alive discharge . Our model indicates that the SOFA score is strongly related to vital status. PVAs are positively associated with alive discharge but there is not enough evidence that PVAs provide a more accurate indication of death prognosis than the SOFA score alone.